The Differences of Food Compositions in Adolescent Metabolic Syndrome in Malang - Sri Andarini; Djanggan Sargowo (The Indonesian Biomedical Journal, 2010)
BACKGROUND: Obesity, especially obesity in adolescent, is a worldwide health problem needing much of our attention because it can continue to be obesity in adulthood. About 50% obese adolescents grew up to be obese adults. It was a concern since it is one of risk factor associated with cardiovascular events including hypertension, dyslipidemia, insulin resistance and stroke. Visceral obesity is correlated with diabetogenic, atherogenic, prothrombotic, pro-inflammation, and abnormal metabolism. The objective of this study was to assess the prevalence of obese adolescents in Malang and to identitfy the differences in food compositions between metabolic syndrome and non-metabolic adolescents.METHODS: Prevalence of obesity was determined by assessing BMI in 20 Senior and Junior High Schools. Metabolic syndrome was diagnosed using IDF criteria; waist circumference of >80cm and >90cm for female and male, respectively, and increased triglyceride and decreased HDL concentration levels. The food composition was assessed using food recalls, and then regression linier test was done to define the correlation between food intake and the components of metabolic syndrome.RESULTS: The prevalence of adolescent obesity in Malang had reached 3.32%, with the prevalence of obesity in male subjects higher than in female subjects, i.e. 54.1% compared to 45.9%. The boys had higher mean for height and weight than the girls did, however, the BMI was higher in girls rather than boys. The difference of fat in food composition was significantly higher for the metabolic groups (p=0.031), but the carbohydrate did not significantly differ between the two groups (p=0.407).CONCLUSIONS: The prevalence of adolescent obesity in Malang had reached 3.32%, with the prevalence of 54.1% in male and 45.9% in female. From the statistics test, fat intake showed a significant difference between metabolic syndrome and non-metabolic syndrome groups, but other food compositions didn’t.KEYWORDS: obesity, metabolic syndrome, adolescent